O Tempo para a Lingüística e para a Psicanálise - Souza, Silvania Fernandes de (2010)
This dissertation discusses the issue of time in the interface between linguistics and psychoanalysis. To this end, we seek to understand how the time factor acts as an agent of transformation of language, and as a producer of new meanings for the subject under analysis. In this sense, we follow Saussure s teachings as regarding the language as a system of signs aimed at understanding the process of mutability of language, which, in the Saussurean conception, occurs mainly due to the passage of time. The dialogue with psychoanalysis is conducted based on Lacan s design, for whom the unconscious is structured like a language . In this discussion, the notion of timelessness of the unconscious in Freud is always present, because the cut at the time of the session is conducted based on the theory that the unconscious is timeless. The Saussurean linguistics allows us to find traces that point to change within the sign and this leads us to the realization that the new meanings of the subject under analysis appear as a result of a movement similar to the shifts and changes that take place within the sign due the passage of time. However, what differs in the analysis is that it is not a change resulting from the passage of time, but from the cut of the time that passes.